Assessment of total phenolic, total flavonoid, metal contents and antioxidant activities of Trametes versicolor and Laetiporus sulphureus - Bulam, Sanem; Karadeniz, Mertcan; Bakir, Temel Kan; Ünal, Sabri (Uniwersytet Przyrodniczy w Lublinie, 2022)
Antioxidant activities, metal contents, total phenolics and flavonoids were analyzed for Trametes versicolor and Laetiporus sulphureus collected from Kastamonu region by using ICP-OES and spectrophotometric methods. Antioxidant activity of mushroom extracts were expressed as percentage of DPPH radicals inhibition and IC50 values. Percentage of inhibition ranged from 15.83 to 61.03% and IC50 value was found 5.33 mg/mL for L. sulphureus and % inhibition ranged from 7.27 to 20.47% and IC50 value was found 18.10 mg/mL for T. versicolor. The content of phenols in methanolic extracts expressed in gallic acid equivalents varied between 77.41±1.10 and 272,70±2.26 mg/g for T. versicolor and L. sulphureus respectively. Also the content of flavonoids in methanolic extracts expressed in quercetin equivalents varied between 13.82±0.21 and 44.29±0.54 mg/mg for T. versicolor and L. sulphureus, respectively. As a result the significant linear correlation was corroborated between the values for the total phenolic content and antioxidant activity of this mushroom. In addition, all samples were analyzed by ICP-OES to obtain the concentration of Co, Cu, Cd, Pb, Ni, Cr, Na, Ca, Al, Fe, Zn, Ba, P, Mg, As, Mn and B. While maximum and minimum metal contents of mushrooms were found as mg/kg for Na (1.88-2.09), Mg (4.59-6.77), P (17.11-24.52), Ca (0.49-23.91) and Fe (0.49-3.84), the maximum and minimum trace metal contents of mushrooms were found as µg/kg for Cr (8.23-35.27), Ni (41.51-180.99), Cu (36.36-123.93).
Keywords: total flavonoid; Science; Q; Trametes versicolor; antioxidant activity; Plant culture; QD415-436; Biochemistry; SB1-1110; Laetiporus sulphureus; phenolic content; metal content